(untitled) (Configurazioni. Research on contemporary poetry, 2023)
The essay outlines some major aspects of Antonella Anedda’s relationship to the visual culture. More precisely, it points out two dis-identifying devices discernible in her writerly gaze: the one that disobeys to the distance between the spectator and the work of art and the one that carves out a detail from the whole painting. These hypotheses are verified on some samples taken from Anedda’s La vita dei dettagli (2009).